2018
DOI: 10.1159/000494389
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Response to Subcutaneous <b><i>Dermatophagoides pteronyssinus</i></b> Immunotherapy in Children with Allergic Rhinitis and Asthma Is Independent of Sensitization to <b><i>Blomia tropicalis</i></b> Allergens

Abstract: Background: Dermatophagoides pteronyssinus (DP) and Blomia tropicalis (BT) are the dominant house dust mites inducing allergic diseases in tropical climates. It is not known whether the efficacy of DP subcutaneous immunotherapy (SCIT) is similar in patients sensitized to DP alone or to both DP and BT. Method: Ninety-five children (5–17 years old) affected by asthma with rhinitis and sensitized to both DP and BT received 3 years of DP-SCIT. Clinical symptom and medication scores, serum-specific IgE and IgG Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…The EAACI proposed that the increase in serum sIgE and the symptoms after exposure to allergens are the only criteria for diagnosing allergy at present and are also the selection criteria for AIT [ 36 ]. However, the efficacy of AIT based on this standard is only 52–86.9% [ 37 , 38 , 39 ]. Therefore, many studies have been conducted on these biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The EAACI proposed that the increase in serum sIgE and the symptoms after exposure to allergens are the only criteria for diagnosing allergy at present and are also the selection criteria for AIT [ 36 ]. However, the efficacy of AIT based on this standard is only 52–86.9% [ 37 , 38 , 39 ]. Therefore, many studies have been conducted on these biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Изолированная сенсибилизация к недерматоглифным клещам встречается только в 1,5 % случаев, в остальных она сочетается с Dermatophagoides. Показана клиническая эффективность и безопасность АСИТ аллергеном клещей Dermatophagoides у детей с БА и АР, при наличии косенсибилизации к клещам Blomia, Lepidoglyphus независимо от метода терапии [52]. Это связано, по-видимому, с тем, что, несмотря на стандартизацию лечебных аллергенов по Der p(f) 1 и Der p(f) 2, они содержат и другие белки, которые могут служить возможной причиной эффективности при сенсибилизации к другим клещевым аллергенам.…”
Section: психиатрическоеunclassified
“…17 Allergen immunotherapy has been extensively studied and demonstrated to be effective in multiple randomised controlled trials for D. pteronyssinus and D. farinae, 43 whereas only small-scale studies reported clinical response to AIT with Dermatophagoides extracts in patients who are co-sensitised to both Dermatophagoides and B. tropicalis. 44,45 It is uncertain if polysensitised patients with predominantly B. tropicalis reactivity may benefit from AIT, and no recommendation can be made about patients monosensitised to this mite.…”
Section: Not At All Bothersomementioning
confidence: 99%